(3QaY GdSDGd ef KZQ OejGWs - (3SdjeGf Gdadcjs
(3ChdgG (B:s
(3eGbhdce QVi Gddg JYGdi Yfce hfaY HYdhece GdeSdejf ai bhd GHf GdTGWQ QMeg Gddg ai HGH GdSgGe Jbhe GdchGcH ddWGdY hJONd s
(3BNQgG (B:s
(3hjSJYedhf cdGefgeG ai HGH GdEJUGdGJ hGdGLJeGYGJ Edi ZjQ Pdc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B90 - (3U(B93s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B272s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B131) s
Keywords: (3Gdadcs